miR-451 suppresses the NF-kappaB-mediated proinflammatory molecules expression through inhibiting LMP7 in diabetic nephropathy - Sun, Yan; Peng, Rui; Peng, Huimin; Liu, Handeng; Wen, Li; Wu, Tianhui; Yi, Hong; Li, Ailing; Zhang, Zheng (Molecular and cellular endocrinology, 2016)
Activation of nuclear factor -kappa B (NF-κB) is associated with inflammation in the progression of diabetic nephropathy (DN). MiR-451 is closely linked to renal damage in DN. Large multifunctional protease 7 (LMP7), an immunoproteasome subunit, can activate NF-κB. However, it remained unclear whether miR-451 affected NF-κB-induced inflammation by regulating LMP7 in DN. In this study, deep sequencing, in situ hybridization, quantitative real-time PCR, dual-luciferase reporter gene assays, western blot and chromatin immunoprecipitation were respectively used. For the results, we found that miR-451 was markedly downregulated in the kidneys of db/db mice, PBMCs of DN patients and mesangial cells (MCs) cultured in high glucose conditions. Furthermore, miR-451 directly targeted LMP7 expression to inhibit NF-κB activity, and down-regulated transcription of proinflammatory molecules in MCs. More importantly, in the kidneys of db/db DN mice, increasing miR-451 level inhibited LMP7/NF-κB activity, and attenuated the urinary microalbumin excretion, blood glucose, and glomerular injury. In conclusion, these results provide new insights into the regulation of miR-451 via the LMP7/NF-κB central inflammatory pathway during progression of DN. [Display omitted] •miR-451 was knockdown and LMP7 was overexpression in kidneys of db/db DN mice and high glucose cultured MCs.•miR-451 directly inhibited LMP7 to decrease NF-κB-mediated inflammation in H-MC and in the kidneys of db/db DN mice.•overexpression of miR-451 attenuated glomerular damage in db/db mice.